Sister talk: Investigating an older sibling's responses to verbal challenges. (June 2018) - Friedland, Joanna; Mahon, Merle
Children's linguistic and social skills develop through play with siblings, but there is little research into sibling interaction using naturally occurring data. This conversation analytic case study presents an evidence-based account of how an older sibling responds to verbal challenges from her younger sibling during free play at home. The older sibling employs prosodic, rhetorical and linguistic devices to deflect challenges while avoiding conflict. She does this by acknowledging the grounds of the challenge, before invoking privileged information or epistemic differences to reject it. Structurally, the older sibling inserts extended digressions which obfuscate challenges by engaging the challenger and switching topic. These phenomena blur the traditional accept/reject response dichotomy. The findings provide insight into the complexity of a 5-/6-year-old's challenge-defence strategies and highlight the importance of face preservation and mitigation of disagreement. We propose that the ability to respond to challenges while maintaining intersubjectivity is a component of communicative competence.